Vocabulary for IELTS advanced with answers : self-study vocabulary practice - Cullen, Pauline, ....- (Cambridge : Cambridge University Press, 2015)
Covering all the vocabulary needed for the IELTS tests, this handy practice book offers useful tips on vocabulary learning and how to approach the exam. Vocabulary is presented in realistic contexts and typical learner errors are highlighted to help candidates avoid classic pitfalls. The topic-based unit approach means the material can easily be used to supplement an exam coursebook.
Official Cambridge preparation materialss for IELTS
Keywords: Engels -- Taalgebruik